2013
DOI: 10.3892/ijmm.2013.1540
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of nimodipine on cerebrovascular function in chronic alcoholic encephalopathy

Abstract: In the present study, we used chronic gavage administration of alcohol with gradual increases in alcohol concentration and volume to generate a rat model of chronic alcohol intoxication. We measured the changes in biological, behavioral, pathological and vascular injury-related molecular biological markers, and explored the effects of nimodipine intervention on alcohol intoxication. We found that chronic alcohol consumption induced a variety of behavioral abnormalities, accompanied by severe pathological chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…18 Meanwhile, Li et al found that TET could protect rat from alcoholic-induced chronic alcoholic encephalopathy. 7 These results were consistent with our finding, and confirmed TET may serve as a neuroprotective role in BUP-treated SH-SY5Y cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…18 Meanwhile, Li et al found that TET could protect rat from alcoholic-induced chronic alcoholic encephalopathy. 7 These results were consistent with our finding, and confirmed TET may serve as a neuroprotective role in BUP-treated SH-SY5Y cells.…”
Section: Discussionsupporting
confidence: 92%
“…Tetramethylpyrazine (TET) is an alkaloid that originally extracted from a traditional Chinese herbal medicine Ligusticum chuanxiong. 7,8 TET has been used as an effective compound to remedy patients with kidney, heart and brain diseases. [9][10][11] In addition, TET also has been reported to provide neuroprotective effect against ischemic brain damage in rats.…”
Section: Introductionmentioning
confidence: 99%
“…It can expand the cerebral blood vessels, improve the cerebral circulation, and protect the brain. [6,7] Studies have shown that nimodipine could improve cognition in adult mice by reducing neuronal damage [8] and our previous research found pretreatment with nimodipine can prevent postoperative cognitive dysfunction (POCD) on aged rats by reducing hippocampal apoptosis rate. [9] However, its clinical effect remains to be discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of a calcium antagonist nimodipine may partly inhibit the apoptosis of neurons in the hippocampus and improve cognitive function following WBRT. Previous studies on cerebral ischemia, brain injury, chronic alcoholic encephalopathy, subarachnoid hemorrhage or cerebral hemorrhage demonstrated that calcium antagonists may exert a protective effect on brain function (12,(35)(36)(37)(38). The expression levels of calcium-associated genes decreased following cerebral ischemia, leading to inhibition of L-type calcium channels, which in turn may induce post-ischemic neuronal death.…”
Section: Discussionmentioning
confidence: 99%